Exploring Acetabular Index Pattern In Pakistani Healthy Children Aged 1-8 Years - Ehsan, Alina; Hussain, Sajjad; Anwer, Muhammad Akhter; Bhatti, Anisuddin (Journal of Rawalpindi Medical College, 2025)
Objective: To determine the acetabular index values of healthy Pakistani children aged 1 to 8 years and to identify the prevalence of primary acetabular dysplasia, which may progress to hip dislocation or resolve to a normal hip. Method: This cross-sectional study includes radiographic evaluation for acetabular index (AI) values in healthy children aged 1–8 years. The study includes pelvis radiographs retrieved from the data database of Ziauddin Hospital, Karachi, exposed for reasons other than hip dysplasia. Voyager Web 4.0 was used to measure the acetabular index on each radiograph. SPSS version 23 was used to conduct statistical analysis according to age, gender, and laterality. Results: The AI values of healthy Pakistani children in the age group 1 year were 19.440 ±0.25 in boys and 19.450 ±0.28 in girls. That progressively decreased to 11.460 ±0.84 in boys and 11.190 ±0.48 in girls, at 8 years of age. The Acetabular Index (AI), when compared for age, gender, and laterality, was found statistically non-significant (t=0.53, p=0.59). Acetabular Index (AI) had an inverse relationship with age (correlation coefficient r = ¬0.96, p=0.001). For every 1-year increase in age, there was a decrease of 1.17 degrees. Conclusion: The study revealed acetabular index values of healthy Pakistani children aged 1-8 years, within normal declared values (mean AI 220) for all age groups & gender. Contrary to the published data, AI levels were somewhat higher among boys than girls at 8 years of age. The study found no case with a high acetabular value (AI >250). However, AI levels decrease with the increase in age. Keywords: Acetabular index, biological variation, Hip Dysplasia, Congenital hip dislocation, Healthy children, Pakistan